Gender Violence & Human Rights: Seeking Justice in Fiji, Papua New Guinea and Vanuatu - Biersack, Aletta; Jolly, Margaret; Macintyre, Martha (ANU Press, 2016)
The postcolonial states of Fiji, Papua New Guinea and Vanuatu operate today in a global arena in which human rights are widely accepted. As ratifiers of UN treaties such as the Convention on the Elimination of All Forms of Discrimination against Women and the Convention on the Rights of the Child, these Pacific Island countries have committed to promoting women's and girls' rights, including the right to a life free of violence. Yet local, national and regional gender values are not always consistent with the principles of gender equality and women's rights that undergird these globalising conventions. This volume critically interrogates the relation between gender violence and human rights as these three countries and their communities and citizens engage with, appropriate, modify and at times resist human rights principles and their implications for gender violence. Grounded in extensive anthropological, historical and legal research, the volume should prove a crucial resource for the many scholars, policymakers and activists who are concerned about the urgent and ubiquitous problem of gender violence in the western Pacific.